The Role of E-Government as A Bureaucratic Reform Innovation Infrastructure - Ignatius Novianto Hariwibowo; Rio Ageng Surya Susandy; Agustinus Edi Sutarta; Krist Setyo Yulianto (STI Policy and Management Journal, 2026)
Improving public services is one way to achieve government success. Within the framework of New Public Management, Indonesia created a grand design for bureaucratic reform through Presidential Regulation No. 81/2010. The government also implemented the Electronic-Based Government System (SPBE) as the foundation of e-government to reaffirm its commitment to improving services. This study examines e-government as an infrastructure that moderates the influence of bureaucratic reform and accountability on public services. The data includes the bureaucratic reform index, SPBE, SAKIP (accountability), and public services from provincial governments. The role of e-government as a moderator analyzed using panel regression with secondary data from 31 provincial governments and 186 panels from 2019 to 2024.  By positioning e-government as a moderator, this study explores the role of technology as a platform for public service innovation, a previously unstudied topic. The results show that bureaucratic reform and accountability directly improve public services, but e-government does not strengthen the influence of either. These findings confirm that technology adoption is an innovative tool that accelerates improvements in public service quality. This implies that the government requires digital capacity, data integration, and IT governance to deliver fast, transparent services to citizens without halting procedures.